Methicillin-Resistant Staphylococcus aureus Diabetic Foot Crossed Infection: A Case Report - Reina-Bueno, María (Pathogens, 2020)
This work presents a protocol to prevent the transmission of multidrug-resistant infections. We focus on the Diabetic Foot Unit Podiatry Clinic Area attached to the University of Seville in particular. The most common complication for patients with diabetes is leg ulcers. Together with neuropathy, vasculopathy, and immunological response disorder, these individuals have a high predisposition to developing infections. Staphylococcus aureus is a highly prevalent microorganism in humans which, at times, may act as a pathogen. Due mainly to indiscriminate abuse of antibiotics, the methicillin-resistant strain known by its initials as MRSA is the most extended nosocomial infection globally and is a severe community and hospital healthcare problem. This paper describes compliance with new general recommendations on cleaning, hygiene, and decontamination, in addition to implementation of this specific protocol, after detection of cross infection (healthcare-related infection) in the studied unit in two patients with MRSA-infected ulcers. After an in-depth bibliographical review, strict hand hygiene measures and use of non-sterile gloves were used when treating all patients with a diabetic foot. Finally, we reflect on the need to educate healthcare personnel to guarantee correct prescription of selected antibiotics. The role of the podiatrist in the multidisciplinary team is highlighted not only in terms of management and treatment of lesions in diabetic patients, but also as a healthcare agent for the detection and prevention of MRSA together with other multidrug-resistant infections.